2016
DOI: 10.1002/2016jd025297
|View full text |Cite
|
Sign up to set email alerts
|

Toward understanding the physical link between turbines and microclimate impacts from in situ measurements in a large wind farm

Abstract: Recent wind farm studies have revealed elevated nighttime surface temperatures but have not validated physical mechanisms that create the observed effects. We report measurements of concurrent differences in surface wind speed, temperature, fluxes, and turbulence upwind and downwind of two turbine lines at the windward edge of a utility‐scale wind farm. On the basis of these measurements, we offer a conceptual model based on physical mechanisms of how wind farms affect their own microclimate. Periods of docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 63 publications
2
23
1
Order By: Relevance
“…The aggregate impact of these individual turbine wakes can extend over 50 km downwind of a wind farm, particularly during stable conditions when little atmospheric 10 convection is present to erode the wake (Christiansen and Hasager, 2005;Platis et al, 2018). Consequences of these wake effects include local changes to surface fluxes that can raise surface temperatures at night due to turbine-induced mixing of the nocturnal inversion (Baidya Roy, 2004;Baidya Roy and Traiteur, 2010;Zhou et al, 2012;Rajewski et al, 2013;Smith et al, 2013;Rajewski et al, 2016;Siedersleben et al, 2018a) and loss of power and revenue for downwind wind farms operating in the wind speed deficit (Nygaard, 2014;Nygaard and Hansen, 2016;Nygaard and Newcombe, 2018;Lundquist et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The aggregate impact of these individual turbine wakes can extend over 50 km downwind of a wind farm, particularly during stable conditions when little atmospheric 10 convection is present to erode the wake (Christiansen and Hasager, 2005;Platis et al, 2018). Consequences of these wake effects include local changes to surface fluxes that can raise surface temperatures at night due to turbine-induced mixing of the nocturnal inversion (Baidya Roy, 2004;Baidya Roy and Traiteur, 2010;Zhou et al, 2012;Rajewski et al, 2013;Smith et al, 2013;Rajewski et al, 2016;Siedersleben et al, 2018a) and loss of power and revenue for downwind wind farms operating in the wind speed deficit (Nygaard, 2014;Nygaard and Hansen, 2016;Nygaard and Newcombe, 2018;Lundquist et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This campaign was a component of the larger CWEX project, which explored the interactions of wind turbines with crops, surface fluxes, and near-surface flows in different atmospheric stability regimes in flat terrain (Rajewski et al, 2013). Research facilitated by the CWEX projects include diurnal changes in observed turbine wakes (Rhodes and Lundquist, 2013), turbine interactions with moisture and carbon dioxide fluxes , LES modelling of turbine wakes in changing stability regimes , nocturnal low-level jet (LLJ) occurrences (Vanderwende et al, 2015), diurnal changes of the microclimate near wind turbines (Rajewski et al, 2016), multiple-wake interactions (Bodini et al, 2017), the evolution of turbine wakes during the evening transition (Lee and Lundquist, 2017), and coupled mesoscalemicroscale modelling (Muñoz-Esparza et al, 2017).…”
Section: Observationsmentioning
confidence: 99%
“…Wind farms extract kinetic energy from the wind, resulting in wakes (Lissaman 1979;Högström et al 1988;Wang and Prinn 2010;Iungo et al 2013;Smith et al 2013). Several studies have found a nighttime warming trend downwind of wind farms (Baidya Roy and Traiteur 2010;Zhou et al 2012;Smith et al 2013;Rajewski et al 2013;Armstrong et al 2016;Rajewski et al 2016), which is likely due to vertical mixing induced by turbine operation. Daytime increases in upward latent heat flux and downward CO 2 flux also occur (Rajewski et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found a nighttime warming trend downwind of wind farms (Baidya Roy and Traiteur 2010;Zhou et al 2012;Smith et al 2013;Rajewski et al 2013;Armstrong et al 2016;Rajewski et al 2016), which is likely due to vertical mixing induced by turbine operation. Daytime increases in upward latent heat flux and downward CO 2 flux also occur (Rajewski et al 2013). As these effects are not negligible, they should be considered in weather models.…”
Section: Introductionmentioning
confidence: 99%